Safety profile of subcutaneous trastuzumab for the treatment of patients with HER2-positive early or locally advanced breast cancer: primary analysis of the SCHEARLY study. (December 2018) - Zambetti, Milvia; Montemurro, Filippo; Morandi, Paolo; Zamagni, Claudio; Brandes, Alba A.; Bisagni, Giancarlo; Cagossi, Katia; Bengala, Carmelo; Gori, Stefania; Iannacone, Claudio; Stell, Alessia; Gianni, Luca
Abstract: Background: Subcutaneous trastuzumab (H SC) is a valuable alternative to the intravenous formulation. This study assessed H SC safety and tolerability in human epidermal growth factor receptor 2 (HER2)+ early/locally advanced breast cancer (EBC/LABC). Methods: SCHEARLY is a prospective, two-cohort, non-randomised, multicentre Italian trial included in the umbrella study UmbHER1, planning a 1-year treatment with H SC 600 mg in HER2+ EBC/LABC. Patients were sequentially assigned to cohort A (N = 121) and B (N = 119) to receive H SC via a handheld syringe and a single-use injection device, respectively. Adjuvant or neoadjuvant treatment included anthracycline-containing regimens followed by H SC plus taxanes and then alone for 18 cycles totally. Results: Two hundred forty patients were enrolled (adjuvant therapy: 81.7%; neoadjuvant therapy: 18.3%), and 201 completed the treatment (early discontinuation was mainly due to intercurrent adverse events [AEs], 7.5%). Overall, the two cohorts displayed similar safety profiles. From H SC start, the rate of treatment-related AEs in the safety population (N = 228) was 3.9% for grade ≥3 AEs; 0.9% for serious AEs (one pleuropericarditis and one anaphylactic shock, both resolved) and 14.5% for cardiac AEs, the most common being the decreased left ventricular ejection fraction (7.9%; mean reduction from the screening to the follow-up visit was 2.9%). No cases of congestive heart failure occurred. The rate of systemic administration-related reactions and local injection site reactions was 68.0% and 21.9%, respectively, mostly of grade 1–2. Conclusions: H SC 600 mg confirmed to be a safe and tolerable option as adjuvant/neoadjuvant therapy in patients with HER2+ EBC and LABC. ClinicalTrials.gov Identifier: NCT01940497. Highlights: Subcutaneous trastuzumab (H SC) confirms to be a safe and tolerable option in patients with HER2-positive early and locally advanced breast cancer. Administration-related adverse events were mostly of grade I–II. Cardiotoxicity was consistent with previous findings. Most patients and healthcare professionals would prefer H SC over intravenous trastuzumab.